Compendium of Key Human Rights Documents of the African Union (Seventh Edition) (Pretoria University Law Press (PULP), 2023)
This is the seventh edition of the Compendium of key human rights documents of the African Union updated to June 2022. It is the first edition published since the untimely passing of Prof Christof Heyns who approached me many years ago with the idea for this Compendium. The Compendium was first published in 2005 and thereafter regularly updated.